INTEGRATING CORPUS AND DISCOURSE APPROACHES TO ANALYZE TERMINOLOGICAL COLLOCATIONS IN ENGLISH AND UZBEK: A COMPARATIVE STUDY (Acta Education, 2025)
Abstract. This article investigates how terminological collocations (fixed combinations of specialized terms) function across English and Uzbek, combining corpus analysis and discourse analysis to reveal patterns of use, frequency, and contextual variation. By integrating quantitative data from specialized corpus and qualitative insights from discourse analysis (nanotechnology), the study aims to uncover how professional and cultural factors shape terminological collocation patterns in both languages. The study will not only identify shared and unique patterns in English and Uzbek terminological collocations but also show how discourse practices shape terminology use. This can contribute to fields like contrastive linguistics, translation studies, and lexicography, and support better bilingual terminology databases. Future research could expand this work by incorporating a larger corpus, including other languages, and exploring diachronic changes in nanotechnology discourse.